Global Financial Shocks and Foreign Asset Repatriation : Do Local Investors Play a Stabilizing Role? - Adler, Gustavo; Djigbenou, Marie-Louise.; Sosa, Sebastian (Washington, D.C. : International Monetary Fund, 2014)
We study the dynamic response of gross capital flows in emerging market economies to different global financial shocks, using a panel vector-autoregressive (PVAR) setting. Our focus lies primarily on the potentially stabilizing role played by domestic investors in offsetting the response of foreign investors to global shocks. We find evidence of such role, but its existence and magnitude depend on the nature of the shock. Local investors play a meaningful stabilizing role in the face of global uncertainty shocks, as well as shocks to long-term U.S. interest rates. However, while in the former case, sizeable asset repatriation largely offsets the retrenchment of non-residents, in the latter case the extent of the offsetting is much more limited. Meanwhile, residents and non-resident behave alike in response to short-term U.S. interest rate shocks, pulling capital away from emerging markets, although magnitudes are not economically significant. The results shed light on the potential impact of the Fed's QE tapering on emerging market economies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet